Intracellular delivery of phosphoinositides and inositol phosphates using polyamine carriers - Ozaki, Shoichiro (The National Academy of Sciences, 2000)
Phosphoinositide signaling regulates events in endocytosis and exocytosis, vesicular trafficking of proteins, transduction of extracellular signals, remodeling of the actin cytoskeleton, regulation of calcium flux, and apoptosis. Obtaining mechanistic insights in living cells is impeded by the membrane impermeability of these anionic lipids. We describe a carrier system for intracellular delivery of phosphoinositide polyphosphates (PIP(n)s) and fluorescently labeled PIP(n)s into living cells, such that intracellular localization can be directly observed. Preincubation of PIP(n)s or inositol phosphates with carrier polyamines produced complexes that entered mammalian, plant, yeast, bacterial, and protozoal cells in seconds to minutes via a nonendocytic mechanism. Time-dependent transit of both PIP(n)s and the carrier to specific cytosolic and nuclear compartments was readily visualized by fluorescence microscopy. Platelet-derived growth factor treatment of NIH 3T3 fibroblasts containing carrier-delivered phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P(2)]-7-nitrobenz-2-oxa-1,3-diazole resulted in the redistribution of the fluorescent signal, suggesting that fluorescent PtdIns(4,5)P(2) was a substrate for phospholipase C. We also observed a calcium flux in NIH 3T3 cells when complexes of carrier and PtdIns(4,5)P(2) or inositol 1,4,5-trisphosphate were added extracellularly. This simple intracellular delivery system allows for the efficient translocation of biologically active PIP(n)s, inositol phosphates, and their fluorescent derivatives into living cells in a physiologically relevant context.